Anxiety Enhances Recall of Supernatural Agents. Issue 1 (2nd January 2022) - Swan, Thomas; Halberstadt, Jamin
ABSTRACT: The motivational account of religious belief – that belief fulfills some psychological need – has been historically popular, and recent studies have identified a causal role for anxiety in particular. However, the cognitive mechanisms by which anxiety ultimately produces religious belief are unclear. In two studies, we show that anxiety intensifies a known cognitive bias to recall supernatural agents via preferential processing of the threatening characteristics of these agents. Across the two studies, participants exposed to an anxiety manipulation at encoding (but not at retrieval) exhibited a stronger recall bias for supernatural agents than controls, regardless of how anxiety was elicited and regardless of participants' religiosity. The results suggest that people in anxious states are more likely to remember and accumulate representations of supernatural or "godlike" agents than people in non-anxious states, potentially biasing them toward religious belief in these agents. This work therefore lends support and detail to the motivational account, addresses the puzzle of why some malevolent gods attract believers, and, by illustrating the importance of anxiety in recall for supernatural agents, argues for the construction of cognitive-motivational models of religious belief.